2007
DOI: 10.1108/00907320710729337
|View full text |Cite
|
Sign up to set email alerts
|

Toward large scale assessment of information and communication technology literacy

Abstract: PurposeThe purpose of this paper is to provide guidance to those contemplating or preparing to administer a large scale information literacy assessment such as the ETS ICT assessment instrument. The case studies and literature review provide real life examples of how to consider implementing the ETS ICT instrument with special attention to issues such as collaboration, timing, marketing, budgeting, and developing a strategy that includes a discussion of how testing results will inform campus information litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
5
0
4
Order By: Relevance
“…En este marco, es importante preguntarse sobre dos categorías que se abren como importantes: la alfabetización y la competencia digital. La nueva sociedad de la información y comunicación, pone de manifiesto la necesidad de una ciudadanía capaz de acceder, evaluar de manera crítica, organizar, interpretar la información y comunicarse a través de múltiples formatos digitales, en constante transformación (Somerville, Lampert, Dabbour, Harlan & Schader, 2007). La enorme proliferación de las TIC ha provocado que, cada día de forma más evidente, los individuos tengan que enfrentarse a situaciones que requieren la utilización de nuevas habilidades técnicas, cognitivas y sociales.…”
Section: 2-la Competencia Digital Y Las Nuevas Alfabetizacionesunclassified
“…En este marco, es importante preguntarse sobre dos categorías que se abren como importantes: la alfabetización y la competencia digital. La nueva sociedad de la información y comunicación, pone de manifiesto la necesidad de una ciudadanía capaz de acceder, evaluar de manera crítica, organizar, interpretar la información y comunicarse a través de múltiples formatos digitales, en constante transformación (Somerville, Lampert, Dabbour, Harlan & Schader, 2007). La enorme proliferación de las TIC ha provocado que, cada día de forma más evidente, los individuos tengan que enfrentarse a situaciones que requieren la utilización de nuevas habilidades técnicas, cognitivas y sociales.…”
Section: 2-la Competencia Digital Y Las Nuevas Alfabetizacionesunclassified
“…La SIC pone de manifiesto la necesidad de una ciudadanía capaz de acceder, evaluar de manera crítica, organizar, interpretar la información y comunicarse a través de múltiples formatos digitales, en constante transformación (Somerville, Lampert, Dabbour, Harlan & Schader, 2007).…”
Section: La Alfabetización Y La Competencia Digitalunclassified
“…Incluye la capacidad de utilizar las TIC como una herramienta para investigar, organizar, evaluar y comunicar información, así como el conocimiento de las cuestiones éticas y legales que rodean el acceso y uso de la información (Somerville et al, 2007). Según este modelo, la alfabetización digital o competencia digital no puede ser definida principalmente como el dominio de las habilidades técnicas, sino que debe centrarse especialmente en las habilidades cognitivas fundamentales, y en la aplicación de las destrezas técnicas y conocimientos .…”
Section: Marcos Y Modelos De La Competencia Digitalunclassified
“…Sommerville, et.al., posit collaboration between invested stakeholders and administrators "will advance the likelihood of campus consideration of large-scale assessment results." 6 Additionally, Bridgland and Whitehead found that teaching faculty responded better to assessment efforts when they were approached directly by librarians with whom they already had a working relationship. 7 They theorize that advocating for library assessment to both administrators and teaching faculty was necessary, arguing that "although the organization provides a framework, it is through more subtle connections with individuals that successful collaboration and knowledge building occurs."…”
Section: Literature Reviewmentioning
confidence: 99%